Do acordo à reforma ortográfica: a emergência de uma fórmula? - Gibin, Fernando Curtti (2011)
The aim of this research, based on the French Discourse Analysis theoretical and methodological approach, is analyzing discursively how Folha de S. Paulo (a Brazilian newspaper of significant circulation) narratively published the Portuguese Language Orthographic Agreement of 1990, which came into force in January 1st, 2009. As temporal outline, we established the period from January 1st, 2008 (a year before the effective coming into force of the agreement among the Portuguese language countries) to January 1st, 2010 (a year after it comes into force). Our main purpose is understanding during this period how the verbal sequence acordo ortográfico (spelling agreement), when it slides to reforma ortográfica (spelling reform), can be understood as a formula: an object which is describable in language categories and whose destiny at the same time invasive and continuously questioned inside the public discourses is determined by language practices and by the state of opinion and power relations in a specific moment in the very heart of the public space. (Krieg-Planque, 2009, p. 14). In other words, we have the objective of verifying on this paper during this established period how this syntagm reforma ortográfica, even though it is formally stable in the point of view of the linguistic description and explanation, is performed by the medium work in the public space discourses as a sequence both shared and problematic, knowing a discursive regime that makes it a formula.